Lecture 1. “To the 100th anniversary of Mykhailo Fedorovich Deigen” by Prof. Bella D. Shanina - Shanina, B.D. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2018)
SPQEO Journal continues the rubric “Lectures, Presentations, etc.” This issue is devoted to the 100th anniversary of Prof. Mykhailo Deigen. These presentations were represented in June, 2018. Both biographical facts and scientific features of Prof. M. Deigen are available.